Restoring Faith and Form: Reconstruction of Bunga-Dyo (Rato Matsyendranatha) Temple at Bungamati (Journal of Science and Engineering, 2026)
The paper analyses the community participation in the reconstruction of the Rātō Matsyendranātha temple at Buṅgamati. It was severely damaged in the 2015 Gorkha earthquake and its reconstruction completed after ten years, with a story of resilience, faith and cultural continuity. The reconstruction process changed from contracted construction to a community-led process. This paper further intends to study the process of community building in the core belief system integrated with socio-cultural practices, the challenges of involving stakeholders, local community, national and foreign agencies, which in due course delayed the reconstruction process. The paper claims that the initially ignored local community’s active participation proved vital in restoring and conserving the temple and the site, alongside keeping the faith with the temple intact. The Rātō Matsyendranātha temple reconstruction process that spanned for almost a decade largely saw local community as the primary custodians who ensured ‘authentic’ traditional restoration contesting with the modern-day engineering practice. This study further delves into how reconstruction process can delay due to multifarious challenges involving stakeholders along with local and trans-local agencies. Thus, focusing on the study of community building integrated with socio-cultural practices, also the role of cultural devotion that shaped the successful reconstruction in form and function, giving valuable insight into Nepal’s heritage reconstruction. The paper concludes by reiterating that the restoration of heritage structures is a multiple stakeholder engagement approach where the immediate community’s involvement is crucial in understanding the faith and form of the structure. Hence, it becomes essential to identify the areas of expertise where the local community can equally participate with the experts in the field to ensure the proper reconstruction process, in which the ownership and sense of belonging could be an integral part of such reconstruction process.